2015
DOI: 10.1086/684123
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Foster Parent Training with Parent-Child Interaction Therapy: Evidence from a Randomized Field Experiment

Abstract: Objective Research indicates that foster parents often do not receive sufficient training and support to help them meet the demands of caring for foster children with emotional and behavioral disturbances. Parent-Child Interaction Therapy (PCIT) is a clinically efficacious intervention for child externalizing problems, and it also has been shown to mitigate parenting stress and enhance parenting attitudes and behaviors. However, PCIT is seldom available to foster families, and it rarely has been tested under i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“… 28 Each of these studies noted similar decreases in child behavior problems and increases in positive parenting skills. It is interesting to note that several studies have also shown PCIT to be effective with nonparental caregivers such as foster parents 29 , 30 and participants in a kinship care program. 31 …”
Section: Treatment Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Each of these studies noted similar decreases in child behavior problems and increases in positive parenting skills. It is interesting to note that several studies have also shown PCIT to be effective with nonparental caregivers such as foster parents 29 , 30 and participants in a kinship care program. 31 …”
Section: Treatment Effectivenessmentioning
confidence: 99%
“…Notably, when researchers compared the use of individual PCIT to group PCIT, significant improvements were noted in child conduct problems, parenting stress, and children’s adaptive functioning in both formats. 83 Such groups have included families of predominantly low socioeconomic backgrounds in a community-based setting, 82 women in a correctional facility, 26 , 29 and families with a history of child abuse or at risk of child maltreatment. 28 in addition to such lack of outcome differences between formats, a group treatment context may be more cost effective and foster a supportive community between participants.…”
Section: Format-based Adaptationsmentioning
confidence: 99%
“…Several randomized controlled trials have been conducted in the USA to meet the need for parental sensitivity-focused, evidence-based prevention and intervention programs for this high-risk population. Examples of effective interventions for foster care are Attachment and Biobehavioral Catch-up (ABC; [ 23 ]), Multidimensional Treatment Foster Care for Preschoolers (MTFC-P; [ 21 ]), Parent-Child Interaction Therapy (PCIT; [ 66 , 67 ]), Promoting First Relationships (PFR; [ 68 , 69 ]), and Parent Management Training-Oregon Model (PMTO; [ 70 ]). However, little is known about the effectiveness of these or comparable prevention and intervention programs in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of PCIT with children with histories of maltreatment have focused on biological parents (Chaffin et al, 2004; Chaffin, Funderburk, Bard,Valle, & Gurwitch, 2011) or traditional foster caregivers (McNeil, Herschell, Gurwitch, & Clemens-Mowrer, 2005; Mersky, Topitzes, Grant-Savela, Brondino, & McNeil, 2014; Mersky, Topitzes, Janczewski, & McNeil, 2015) using full-protocol PCIT. A randomized trial of PCIT as a foster parent training model for non-kinship foster parents caring for children with externalizing behavior problems in the clinical range demonstrated improvement in both child externalizing and internalizing child symptoms (Mersky et al, 2014) as well as caregiver parenting stress (Mersky et al, 2015).…”
Section: Child Directed Interaction Trainingmentioning
confidence: 99%
“…A randomized trial of PCIT as a foster parent training model for non-kinship foster parents caring for children with externalizing behavior problems in the clinical range demonstrated improvement in both child externalizing and internalizing child symptoms (Mersky et al, 2014) as well as caregiver parenting stress (Mersky et al, 2015). However, kinship caregivers were intentionally excluded from these studies.…”
Section: Child Directed Interaction Trainingmentioning
confidence: 99%